Inger Dübeck: Fra gammel dansk til ny svensk ret. Den retlige forsvenskning i de tabte territorier 1645-1683. (Rigsarkivet/G. E. C. Gad, København 1987). 128 s., ill., 146,40 kr. - J. V. Jespersen, Knud (Historie/Jyske Samlinger, 1989)
-